Effective Partnerships: Examining How Environmental Non-Governmental Organisations (Engos) Manage Communications With Corporations - Chooi, Irene Mei Ting (2022)
Stakeholder demand for corporations to demonstrate greater ecological responsibility, as well as funding and mission pressures for Environmental NonGovernmental Organisations (ENGOs), has led to a rise in cross-sector partnerships between the two. While such partnerships can be mutually beneficial, research shows ENGOs suffer more risks. This study aimed to produce an in-depth and comprehensive understanding of cross-sector partnerships between ENGOs and corporations, specifically in terms of how ENGOs use communication tactics to manage such relationships. A phenomenological, in-depth, semi-structured qualitative research was conducted with five members of ENGOs with a minimum two-year experience in communicating with corporations. The research carried out via one-on-one online interviews verify ENGOs are aware of these risks and have developed communication tactics to protect themselves. The plan starts with screening potential corporate partners and culminates in agreements and legal contracts before official partnerships begin. There are two novel findings in this research. The first being that ENGOs in Malaysia spend a lot of time in the initial screening phase educating their potential corporate partners of the ENGO’s mission and methods as a form of risk aversion. The other novel finding is that some ENGOs in Malaysia perceive short-term partnerships to be greenwashing attempts. These findings highlight Malaysian ENGOs are capable of protecting themselves in a cross-sector partnership. However, they are still at a disadvantage in the partnership because of an imbalance in resources. Ultimately, Malaysian ENGOs are aware of their disadvantages but are still iii willing to work with corporate partners to pursue their environmental mission. The study could be considered to motivate budding ENGOs to improve their self-protection mechanisms via legal contracts and also inspire corporations to consider long-term sustainability partnerships.